The state of child nutrition in Ethiopia: an umbrella review of systematic review and meta-analysis reports - Shimels Hussien Mohammed; Tesfa Dejenie Habtewold; Amanuel Godana Arero; Ahmad Esmaillzadeh (BMC, 2020)
Abstract Background Malnutrition remains to be a major public health problem in developing countries, particularly among children under-5 years of age children who are more vulnerable to both macro and micro-nutrient deficiencies. Various systematic review and meta-analysis (SRM) studies were done on nutritional statuses of children in Ethiopia, but no summary of the findings was done on the topic. Thus, this umbrella review was done to summarize the evidence from SRM studies on the magnitude and determinants of malnutrition and poor feeding practices among under-5 children in Ethiopia. Methods PubMed, Embase, Scopus, Web of Sciences, Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, and Google Scholar were searched for SRM studies on magnitude and risk factors of malnutrition and child feeding practice indicators in Ethiopia. The methodological quality of the included studies was assessed using the Assessment of Multiple Systematic Reviews (AMSTAR) tool. The estimates of the included SRM studies on the prevalence and determinants of stunting, wasting, underweight, and poor child feeding practices were pooled and summarized with random-effects meta-analysis models. Result We included nine SRM studies, containing a total of 214,458 under-5 children from 255 observation studies. The summary estimates of prevalence of stunting, underweight, and wasting were 42% (95%CI = 37-46%), 33% (95%CI = 27-39%), and 15% (95%CI = 12-19%), respectively. The proportion of children who met the recommendations for timely initiation of breastfeeding, exclusive breastfeeding during the first 6 months, and timely initiation of complementary feeding were 65, 60, and 62%, respectively. The proportion of children who met the recommendations for dietary diversity and meal frequency were 20, and 56%, respectively. Only 10% of children fulfilled the minimum criteria of acceptable diet. There was a strong relationship between poor feeding practices and the state of malnutrition, and both conditions were related to various health, socio-economic, and environmental factors. Conclusion Child malnutrition and poor feeding practices are highly prevalent and of significant public health concern in Ethiopia. Only a few children are getting proper complementary feeding. Multi-sectoral efforts are needed to improve children's feeding practices and reduce the high burden of malnutrition in the country.